THE EFFECTIVENESS OF OFFLINE LEARNING TOWARDS INCREASING LEARNING ACHIEVEMENT OF CLASS IV STUDENTS IN GPID PALU CHRISTIAN ELEMENTARY SCHOOL DURING COVID-19 - Jeisi Riska Merdekawati Mentu; Rizal Rizal (Jurnal Dikdas, 2022)
This study aims to determine the role of offline learning on student learning outcomes for class IV SD Kristen GPID Palu. The type of research in this study is a type of qualitative descriptive research. The subjects in this study were all class IV SD Kristen GPID Palu students for the 2020/2021 academic year with a total of 30 students consisting of 15 males and 15 females. From the results of the research, the role of offline learning on the learning outcomes of 4th grade students of SD Kristen GPID Palu was quite effective. The teacher carries out the process, namely planning: RPP, smartphones, books and other media), implementation: delivery of question and answer material and giving assignments, and valuation: checking assignments collected by students and writing them down in reports. The problems experienced by teachers in carrying out Offline classes during the Covid-19 pandemic for class IV SD Kristen GPID Palu students were limited facilities and knowledge about technology, making offline learning, lack of parental assistance during learning caused students to lack discipline, student complaints about assignments which accumulates a lot.